2016
DOI: 10.4148/1051-0834.1032
|View full text |Cite
|
Sign up to set email alerts
|

Student Expectations and Reflections of a Study Away Course Experience to Washington, D.C.

Abstract: Active, out-of-the-class learning experiences have proven to provide students with a variety of benefits. One way to offer these valuable experiential education opportunities this is through study away to international or domestic destinations. The purpose of this study was to explore students' perceptions of a study away course experience to Washington, D.C. This course was a collaborative effort between two universities. Twenty-two students participated in the study away experience and 21 completed pre-and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the students suggested the selfreflection and peer review activities enabled evaluation of their own work as well as the work of others. By understanding how their work and the work of others could be improved, the students invested mental and emotional engagement in a recent experience, and the students were encouraged to generalize about their own learning (Leggette et al, 2013;Meyers & Arnold, 2016). Additionally, the emergent theme of the instructor as a coach provided students with encouragement to believe they have the capability to be successful writers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Additionally, the students suggested the selfreflection and peer review activities enabled evaluation of their own work as well as the work of others. By understanding how their work and the work of others could be improved, the students invested mental and emotional engagement in a recent experience, and the students were encouraged to generalize about their own learning (Leggette et al, 2013;Meyers & Arnold, 2016). Additionally, the emergent theme of the instructor as a coach provided students with encouragement to believe they have the capability to be successful writers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In terms of locality, Horner (2016) says students benefit by leaving their familiar boundaries of the campus and photographing subjects in unfamiliar places, especially out of state or abroad. This model of travel-based instruction, which is usually seen in study abroad and study away programs, has shown value in the educational experiences of agricultural communications students (Bobbitt & Akers, 2012;Meyers & Arnold, 2016). Travel-or location-based courses can provide high-impact concrete experiential learning for photography students (Homeyer, Leggette, McKim & Walker, 2017).…”
Section: Concrete Experiencementioning
confidence: 99%